2018
DOI: 10.1002/admt.201800033
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oriented Electrospun P(VDF‐TrFE) Fibers via Mechanical Stretching for Wearable Motion Sensing

Abstract: materials, piezoelectric materials, which can convert mechanical shape changes into electric outputs, are particularly favorable to fabricate wearable devices for mechanicalrelated sensing and power generation. [15][16][17] According to material molecular compositions, piezoelectric materials are generally divided into ceramics and polymers. Indeed, even though inorganic piezoelectric materials offer high piezoelectric property, they are mechanically hard and brittle, which have difficulties to be directly app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…Researches of P(VDF-TrFE) in hybrid composite used as touch sensors, energy storage devices, and eld-effect transistors have been widely studied in recent years. [27][28][29][30] Nah et al 31 fabricated and reported the ultrathin P(VDF-TrFE) nanober air lter that can be activated by the dipoles polarization to enhance the ltering efficiency. The electrically activated P(VDF-TrFE) lter demonstrates that the ltering efficiencies were over 88% aer polarization and 94% aer tribo-electrication.…”
Section: Introductionmentioning
confidence: 99%
“…Researches of P(VDF-TrFE) in hybrid composite used as touch sensors, energy storage devices, and eld-effect transistors have been widely studied in recent years. [27][28][29][30] Nah et al 31 fabricated and reported the ultrathin P(VDF-TrFE) nanober air lter that can be activated by the dipoles polarization to enhance the ltering efficiency. The electrically activated P(VDF-TrFE) lter demonstrates that the ltering efficiencies were over 88% aer polarization and 94% aer tribo-electrication.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to quantify movement of key joints during activity can dramatically improve outcomes for rehabilitation and boost athletic performance. [16][17][18][19][20][21] However, the sensing is based on stretching of the fibers, typically unidirectional and poorly suited for integration with substantially rigid electronic components that do not tolerate well to repeated mechanical deformation. [8][9][10] Currently, tracking motion or deducing impact stresses is performed using camera motion tracking systems [11,12] or inertial measurement units (IMUs) that consist of an accelerometer, gyroscope, and magnetometer, typically packaged in a rigid brace or integrated within a band or suit.…”
mentioning
confidence: 99%
“…For example, mapping of insole plantar pressure distribution [50] and detection of impact of water drops [51] were both designed according to longitudinal piezoelectric property. However, transverse piezoelectric property is of especial consideration in most of piezoelectric sensing and energy harvesting applications, including in situ measurement of stress intensity factors during fatigue crack growth, [52] detection of body gestures including angles of elbow bending and directions of a swinging arm, [19] stretchable micromotion sensors for voice recognition [53] and energy harvesting from one finger-striking motion. [54] So, it is required to further explore the contribution of epitaxy process on transverse piezoelectric property.…”
Section: Resultsmentioning
confidence: 99%